Comparison of Patient Controlled Analgesia Alone and Patient Controlled Analgesia with Continuous Infusion Post Total Knee Replacement - Paoin, Jongluk (Journal of Health Science of Thailand, 2018)
Patient controlled analgesia (PCA) has become a widely accepted technique for managing postoperative pain. The objective of this study was to compare the side effects and satisfaction between PCA alone and PCA with continuous infusion. In all, 152 patients were studied, ASA class I or II undergoing total knee replacement and received 0.5% hyperbaric bupivacaine 2.5 ml. At recovery room, the patients were randomized into two groups. Group I received morphine PCA only and group II received morphine PCA with continous infusion 0.5 mg/hr for 24 hours postoperatively. PCA dose of 2 mg and 10 minutes lockout interval were set for both groups. Recorded data included pain score, sedation score, pruritus, nausea, vomiting and satisfaction (24 hrs.). There were no statistical significant differences in patient demographics, ASA physical status, NRS pain score, sedation score, pruritus and patient satisfaction. The incidence of nausea vomiting was significantly lower in PCA alone (28.4%) compared to the PCA with continuous infusion (51.3%) (p-valve 0.004). It was concluded that PCA alone was preferred in management of postoperative total knee replacement pain.